Theory of radiation and absorption of deformed field quanta - Vakarchuk, I.O. (Condensed Matter Physics, 2008)
We calculate the intensity of spontaneous radiation of a system of non-linear quantum eld, where the nonlinearity is due to deformations of the Poison brackets of the generalized coordinates and momenta.